Using Haulage Accidents and Incident Reports to Identify the Impact of Substandard Haul Road Design on Operational Safety - Thompson, Roger (AusIMM, 2010)
Well designed and maintained haul roads are the key to minimising truck haulage on-road hazards and costs, as well as increasing productivity. However, practically designing and managing a haul road for optimal performance is often diff cult to achieve. Poorly designed and built roads exhibit high rolling resistance – a one per cent increase in road rolling resistance can typically reduce speed on ramp by as much as ten per cent - and on the f at by up to 26 per cent. In the current economic climates, investment and operating decisions come under scrutiny. In the long run, this scrutiny returns improved efficiencies and leaner, healthier operations. The focus of this evolving evaluation process should and will certainly fall on haulage operations – simply by virtue of their contribution to overall cost of operations – often in excess of 50 per cent of total costs for deep open-pit mines.Whilst the end result – improved efficiency and reduced cost per ton hauled – is not in itself problematic, it is the route, or process followed to achieve these savings that needs to be carefully managed. We can be guided on this journey by our understanding of how a road is designed, and, critically, the interplay between a good design and safe, cost efficient haulage. This paper brief y summarises the evolution of mine haul road design, from the seminal USBM work of Kaufman and Ault in 1977, through to current geometric, structural, functional and maintenance management design components. These augmented design and management guidelines have been developed over the past decade, both in response to the requirements of mine operators for more safe and efficient haulage systems, and the truck manufacturers’ requirements for a more predictable and controlled operating environment.These developments have been paralleled by the need to minimise haulage hazards, both from a health and safety perspective. Generally, both objectives have been achieved, but with some specific areas of design and operation still presenting ongoing potential health and safety hazards. The paper then summarises current design guidelines for these safety-critical issues, both from a road-design ‘best-practice’ and road management perspectives. Implementation of the approach is seen as a basis for reducing the potential of an under-designed mine road to lead to health and safety defects and secondly as a means of giving haul road safety and performance issues greater prominence in the minds of the road-user, operator, mine planner and designer alike.